Randomised controlled study of laparoscopic versus open reversal of Hartmann’s procedure - Sehsah, Tarek M.; Abd-Raboh, Osama H.; Ismail, Taha A.; Soliman, Soliman M. (International Surgery Journal, 2020)
Background: Laparoscopic reversal of Hartmann’s procedure has been increasingly practiced worldwide since the laparoscopic era. However, so far only a few studies have been published regarding the results of this procedure. Aim of this study was to compare laparoscopic reversal of Hartmann’s (LHR) versus open reversal of Hartmann’s (OHR) procedure regarding to operative time, postoperative pain, hospital stay, postoperative complications and cost. Methods: This study was conducted on 40 patients with Hartmann’s colostomy admitted to the general surgery department, Tanta university hospitals, during the period from February 2017 to August 2019. Results: Regarding operative time, it was with a mean value 274.75±80.65 min in the LHR group and 156.75±32.81 min in the OHR group. The difference in time to pass flatus was with a mean value 1.78±0.68 days in the LHR group and 2.49±0.78 days in the OHR group. The difference in the hospital stay was with mean value 6.1±2.47 days in the LHR group and 9.3±2.20 days in the OHR group. Regarding post-operative complications; 6 patients (30%) developed post-operative complications while in the OHR group 10 (50%). Conclusions: In this era of minimal-access surgery and with increasing attention to fast-track protocols, we believe the laparoscopic approach should be the standard technique for patients undergoing reversal of Hartmann’s procedure. However, laparoscopic reversal of Hartmann’s procedure needs a surgical learning curve.